Environmental Management in the Rincón River Sub-Basin to Preserve Surface Water Quality in the Osa Peninsula - Calvo-Brenes, Guillermo (2025)
A preliminary study assessed water quality in the Rincón River sub-basin using a predictive model based on socio-environmental variables and the Water Quality Index (ICA) Calvo-TEC. Future scenarios were analyzed to determine the impact of various activities on water quality, combining land cover analysis, predictive modeling, and participatory evaluation. The study identified that activities such as the increase in pastures or shrublands have minimal impact, whereas the expansion of permanent or temporary crops and deforestation generate significant negative effects. The results highlight that forest conservation and expansion, as well as responsible management practices, are essential for preserving this resource, particularly in the Golfo Dulce Forest Reserve. Among the predominant crops, African Palm requires special attention due to its high impact in the region. Additionally, sustainable economic activities such as agroforestry systems, reducing agrochemical use, and diversifying income sources are proposed. These strategies allow for balancing water quality protection with the socioeconomic well-being of local inhabitants. Based on these findings, environmental management criteria were established to prioritize water conservation in the sub-basin. These measures are replicable in other areas of the Osa Peninsula, consolidating their utility as a sustainable management model at the regional level.